New record in the number of qubits for a quantum implementation of AES - Li, Zhenqiang; Gao, Fei; Qin, Sujuan; Wen, Qiaoyan (Frontiers in Physics, 2023)
Optimizing the quantum circuit for implementing Advanced Encryption Standard (AES) is crucial for estimating the necessary resources in attacking AES by Grover algorithm. Previous studies have reduced the number of qubits required for the quantum circuits of AES-128/-192/-256 from 984/1112/1336 to 270/334/398, which is close to the optimal value of 256/320/384. It becomes a challenging task to further optimize them. Aiming at this task, we find a method about how the quantum circuit of AES S-box can be designed with the help of automation tool LIGHTER-R. Particularly, the multiplicative inversion in F_2^8, which is the main part of S-box, is converted into the multiplicative inversion (and multiplication) in F_2^4, then the latter can be implemented by LIGHTER-R because its search space is small enough. By this method, we construct the quantum circuits of S-box for mapping |a>|0> to |a>|S(a)> and |a>|b> to |a>|b+ S(a)> with 20 qubits instead of 22 in the previous studies. Besides, we introduce new techniques to reduce the number of qubits required by the S-box circuit for mapping |a> to |S(a)> from 22 in the previous studies to 16. Accordingly, we synthesize the quantum circuits of AES-128/-192/-256 with 264/328/392 qubits, which implies a new record.